Neurodevelopmental and metabolomic responses from prenatal coexposure to perfluorooctanesulfonate (PFOS) and methylmercury (MeHg) in Sprague-Dawley rats - Reardon, Anthony J. F.; Karathra, Jacqueline; Ribbenstedt, Anton; Benskin, Jonathan P.; MacDonald, Amy M.; Kinniburgh, David W.; Hamilton, Trevor; Fouad, Karim; Martin, Jonathan W. (My University, 2019)
Methylmercury (MeHg) and perfluorooctanesulfonate (PFOS) are major contaminants of human blood that are both common in dietary fish, thereby raising questions about their combined impact on human development. Here, pregnant Sprague–Dawley rats ingested a daily dose, from gestational day 1 through to weaning, of either 1 mg/kg bw PFOS (PFOS-only), 1 mg/kg MeHg (MeHg-only), a mixture of 0.1 mg/kg PFOS and 1 mg/kg MeHg (Low-Mix), or of 1 mg/kg of PFOS and 1 mg/kg MeHg (High-Mix). Newborns were monitored for physical milestones and reflexive developmental responses, and in juveniles the spontaneous activity, anxiety, memory, and cognition were assessed. Targeted metabolomics of 199 analytes was applied to sectioned brain regions of juvenile offspring. Newborns in the High-Mix group had decreased weight gain as well as delayed reflexes and innate behavioral responses compared to controls and individual chemical groups indicating a toxicological interaction on early development. In juveniles, cumulative mixture effects increased in a dose-dependent manner in tests of anxiety-like behavior. However, other developmental test results suggested antagonism, as PFOS-only and MeHg-only juveniles had increased hyperactivity and thigmotaxic behavior, respectively, but fewer effects in Low-Mix and High-Mix groups. Consistent with these behavioral observations, a pattern of antagonism was also observed in neurochemicals measured in rat cortex, as PFOS-only and MeHg-only juveniles had altered concentrations of metabolites (e.g., lipids, amino acids, and biogenic amines), while no changes were evident in the combined exposures. The cortical metabolites altered in PFOS-only and MeHg-only exposed groups are involved in inhibitory and excitatory neurotransmission. These proof-of-principle findings at relatively high doses indicate the potential for toxicological interaction between PFOS and MeHg, with developmental-stage specific effects. Future mixture studies at lower doses are warranted, and prospective human birth cohorts should consider possible confounding effects from PFOS and mercury exposure on neurodevelopment.
Keywords: methylmercury; perfluorooctanesulfonate; MeHg; PFOS; contaminants of human blood; Sprague–Dawley rats; toxicological interaction on early development; neurodevelopment; concentrations of metabolites